Manajemen Strategi dalam Meningkatkan Efektivitas Pengelolaan Perguruan Tinggi - Habibi, Surya (Idarah (Jurnal Pendidikan dan Kependidikan), 2020)
This study aims to determine the Strategic Management of Higher Education in Increasing the Effectiveness of PTKIS management in Jambi Province, to reveal the strategies carried out by PTKIS managers and to formulate, implement and evaluate strategies in increasing the effectiveness of PTKIS in Jambi Province. The results showed that the strategic planning of PTKIS in Jambi Province in increasing effectiveness was constrained by several factors as follows: Manager's lack of understanding in implementing strategic management, communication between managers and subordinates is not aligned, strategic goals are not aligned with the actions taken, ideas and innovations are not supported by plans precise, and passive management, as well as manager motivation that only targets personal gain rather than common goals. To overcome the above problems, universities should implement the following actions: be close to stakeholders to understand needs, give autonomy to employees so that they foster an entrepreneurial spirit, managers are actively involved and employees know what the organization wants and have a flexible and simple organizational structure.